Audit Sistem Informasi Menggunakan Framework Cobit 2019 (Studi Kasus: PT X) - Thenu, Gracela Beatrix; Rudianto, Christ (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
This study addresses issues of information system integrity in production that impact the company's operational aspects. The aim is to evaluate the achievement of production information system implementation based on the COBIT 2019 framework. The research employs a qualitative descriptive method, with data collected through interviews and analyzed further. Results indicate that the capability level of domain MEA01 is at 70%, but has not yet reached Level 4 standards. GAP analysis reveals a 1-point discrepancy between the expected and current capabilities, indicating the need for system improvements to meet the company's capability targets. The recommended improvements are intended to enhance the company's operational performance, particularly in production, to be more effective and efficient according to COBIT 2019 guidelines.